A methodology for stratified-charge preparation via low-reactivity fuel multi-injection strategy in intelligent charge compression ignition (ICCI) mode. (1st April 2021) - Li, Zilong; Li, Jing; Huang, Guan; Zhang, Yaoyuan; He, Zhuoyao; Qian, Yong; Lu, Xingcai
Highlights: Gasoline multi-injection strategies in dual-fuel ICCI mode are introduced. The indicated thermal efficiency can reach up to 52% at 8 bar IMEP. Early and high fraction first gasoline injections improve engine performances. Late second gasoline injections decrease combustion noise and PM emissions. Abstract: For optimizing the role of low-reactivity fuel in dual-fuel combustion, a new methodology for stratified-charge preparation via a multi-injection strategy of low-reactivity fuel was introduced on the theory of intelligent charge compression ignition (ICCI). An experimental study was conducted on a modified single-cylinder engine with two common-rail systems fed by commercial gasoline and diesel. The split ratio and injection timing of the first and second gasoline injection were thoroughly studied on engine combustion and emissions. Compared with the gasoline single-injection strategy, the optimized in-cylinder stratified condition can be achieved by gasoline multi-injection strategies. In regards to engine performance, the indicated thermal efficiency can reach up to 52%, enabling an increase of combustion efficiency and low NOx emissions well below 0.4 g/kWh. Among the different gasoline split injection ratios, the combustion and emissions of the 3:1 ratio are most affected by the variation of the gasoline second injection timing. The split gasoline ratio of 2:1 improves combustion efficiency and burning temperature, slightly increasing NOx emissions and combustion noise. Earlier injection timing and higher proportions of the first gasoline injection can ensure that the low-reactive fuel in the cylinder is in a more homogeneous environment, resulting in higher efficiency and lower emissions.